2000
DOI: 10.1074/jbc.m001235200
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor for Advanced Glycation End Products Is Induced by the Glycation Products Themselves and Tumor Necrosis Factor-α through Nuclear Factor-κB, and by 17β-Estradiol through Sp-1 in Human Vascular Endothelial Cells

Abstract: The binding of advanced glycation end products (AGE) to the receptor for AGE (RAGE) is known to deteriorate various cell functions and is implicated in the pathogenesis of diabetic vascular complications. Here we show that AGE, tumor necrosis factor-␣ (TNF-␣), and 17␤-estradiol (E 2 ) up-regulated RAGE mRNA and protein levels in human microvascular endothelial cells and ECV304 cells, with the mRNA stability being essentially invariant. Transient transfection experiments with human RAGE promoter-luciferase chim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
284
2
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 404 publications
(318 citation statements)
references
References 56 publications
23
284
2
9
Order By: Relevance
“…Our findings would be consistent with this, since AGEs are present at much higher levels in cartilage from older adults (39,40), and other RAGE ligands, including S100A4 (41) and HMGB-1 (11), appear to be increased in OA cartilage. The RAGE promoter has been found to contain NF-B binding sites (29), and expression of RAGE is increased by RAGE ligands and inflammatory mediators including TNF␣ (35,42). We found that fibronectin fragments and IL-1␤, which have both been found in cartilage and synovial fluid from patients with OA and RA (30,43), can stimulate chondrocyte RAGE expression.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our findings would be consistent with this, since AGEs are present at much higher levels in cartilage from older adults (39,40), and other RAGE ligands, including S100A4 (41) and HMGB-1 (11), appear to be increased in OA cartilage. The RAGE promoter has been found to contain NF-B binding sites (29), and expression of RAGE is increased by RAGE ligands and inflammatory mediators including TNF␣ (35,42). We found that fibronectin fragments and IL-1␤, which have both been found in cartilage and synovial fluid from patients with OA and RA (30,43), can stimulate chondrocyte RAGE expression.…”
Section: Discussionmentioning
confidence: 75%
“…Polyclonal (AB5484) and monoclonal (MAB5328) antibodies to RAGE were purchased from Chemicon (Temecula, CA). The immunogen for the polyclonal antibody was a synthetic peptide corresponding to amino acids [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] in the N-terminal domain of RAGE, whereas the monoclonal antibody was raised against a recombinant protein containing the extracellular domains of RAGE. A third anti-RAGE antibody (C-20; Santa Cruz Biotechnology, Santa Cruz, CA) was used, and the immunogen was a synthetic peptide corresponding to a region in the carboxy-terminus of RAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperglycemia stimulates an excessive expression of RAGE on pericytes and endothelial cells which results in a deterioration of pericytes. Loss of pericytes leads to vascular damage and clinical expression of retinopathy [27,28]. Moreover, a high level of AGEs in retinal cells induces expression of vascular endothelial growth factor which causes destruction of the blood-retinal barrier and microvascular hyper-permeability, which finally leads to blindness or poorness of vision [29].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…In addition, recombinant TNF enhances amyloid deposition in the Syrian hamster (10). Furthermore, TNF favors the expression of receptors for advanced glycation end products (11), whose interaction with amyloid fibrils is responsible for cytotoxicity and tissue damage (12). Thus, TNF-blocking agents might not only reduce the synthesis of amyloid precursors but also slow amyloid deposition and thus attenuate the consequences of the interaction between amyloid fibrils and their receptors in the cells and tissues (Figure 2).…”
Section: Discussionmentioning
confidence: 99%